Strategi Bauran Pemasaran Non-Konvensional Brainrot dan Anti-Trend dalam Iklan Kitabisa.com - Yuga Adi Kusuma; Yunita Indinabila; Eddy Christijanto (LPPM Stikosa - AWS, 2025)
Amidst audience saturation with digital advertising that is too neat and conventional, a new approach has emerged known as brainrot content and anti-trend, namely a communication strategy that utilizes absurd visuals, hyperbolic humor, and low-budget aesthetics. This study aims to analyze Kitabisa.com's communication strategy in its viral zakat campaign through a social media approach.brain rot, as well as in-depth analysis through Charles Sanders Peirce's semiotics to examine the elements sign, object, and interpreter in advertising content. Furthermore, the campaign was also read through the marketing mix (8P) framework to assess the extent to which this strategy deviates from or transforms traditional marketing norms. The analysis shows that Kitabisa.com strategically packaged religious messages in a fun parody format that resonates with youth digital culture. This strategy successfully generated high engagement on social media, reduced the audience's psychological distance from the issue of zakat, and organically expanded the promotional reach. This campaign demonstrates that absurd humor and unconventional visual communication can be an effective approach in values-based philanthropic digital marketing.